PENGARUH PEMBELAJARAN PROGRAM PENGUATAN KAPASITAS KELOMPOK TERHADAP DINAMIKA KELOMPOK TANI (SUATU KASUS PADA KEBERLANJUTAN PROGRAM PENINGKATAN PENDAPATAN PETANI KECIL DI KABUPATEN SUMEDANG) (THE IMPACT OF GROUP CAPACITY BUILDING PROGRAM ON FARMER GROUP DY - Suwardi, Surachman (Jurnal Ilmu-Ilmu Pertanian, 2010)
The objectives of this study were to analyze the influence of the adoption level of peasants on group capacity building program on dynamic of peasants group. The study object was a peasent group guided through NGP in Sumedang District using observation and interview methods. The respondents were 336 peasants chosen by the disproportionate random sampling. The study was carried out during 23 months beginning from April 2007 to May 2009. The data were collected descriptively and verificatively analyzed using the Structural Equation Model. The results of this study indicated that the adoption level of group capocity building program by peasants influenced significantly on dynamic of peasants' group in the beginner and growing group status.